Economic relations between the Western Balkans and Non-EU countries : how the EU can respond to challenges concerning direct investment, trade and energy security - Vulović, Marina (2023)
Zusammenfassung: The economic and financial crisis of 2008 disrupted the European Union’s (EU) enlargement policy for the Western Balkans. At least since that time, the region has seen greater involvement by economic actors from non-EU countries such as China, Russia, Turkey and the United Arab Emirates (UAE). Their engagement has been most evident in the areas of direct investment, trade and energy security. Investments from these countries can increase the risk of “corrosive capital”, which could have a negative impact on the development of the rule of law and democracy in the Western Balkans. In view of a visibly intensifying rivalry between the EU on the one hand and Russia and China on the other, the question therefore arises as to how the EU can react to and strategically counteract the intensified economic interconnectedness of the Western Balkans with these actors